Economic Value Added, Market Value Added, & Dividend Yield: Pengaruhnya Terhadap Return Saham Perusahaan - Robbi Fernando Saputra; Husnah Nur Laela Ermaya (Coopetition : Jurnal Ilmiah Manajemen, 2022)
Stock return is the result of profit or loss received by investors for their investment activities within a predetermined term. Investors expect to get a return on their investment activities that is greater than the capital that has been issued because in essence investment activities are carried out to increase investors' assets. Microeconomic factors that can cause stock price fluctuations that will have an impact on the company's stock return include Economic Value Added (EVA), market value added (MVA), and dividend yield which is measured by taking into account the cost of capital. This study aims to examine the effect of EVA, MVA, and dividend yield on the stock returns of Kompas 100 index companies on the Indonesia Stock Exchange (IDX) in 2017-2020. The analytical method used is multiple linear regression analysis using STATA version 16. The research sample was determined using a purposive sampling technique and obtained from 32 companies that match the criteria. The results showed partially that EVA had a significant negative effect on stock returns, MVA did not affect stock returns, and dividend yields had a significant positive effect on stock returns. These results illustrate that microeconomic factors can be used by investors in analyzing the fundamentals of a company before making transactions on the Indonesia Stock Exchange.